Ahuman Pedagogy Multidisciplinary Perspectives for Education in the Anthropocene - Beier, Jessie L.; jagodzinski, jan (Palgrave Studies in Educational Futures, 2022)
XVII, 301 p. 12 illus., 3 illus. in color.